2017
DOI: 10.1617/s11527-017-1042-6
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature curing strength enhancement in cement-based materials containing limestone powder

Abstract: With the ongoing sustainability movement, the incorporation of limestone powder in cementitious binders for concrete in the U.S. has become a subject of renewed interest. In addition to accelerating the early age hydration reactions of cementitious systems by providing additional surfaces for nucleation and growth of products, limestone powder is also intriguing based on its influence on low-temperature curing. For example, previous results have indicated that the utilization of limestone powder to replace one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…is is because low temperature restrains the pace of the cement hydration and cement pastes require much longer time to set especially at 0°C. Although the hydration process is demonstrated to proceed at a slower rate in previous study [1,8], low temperature still has a significant impact on the dissolution of clinkers and their reaction with water, resulting in delay in setting time.…”
Section: E Setting Timesmentioning
confidence: 97%
See 2 more Smart Citations
“…is is because low temperature restrains the pace of the cement hydration and cement pastes require much longer time to set especially at 0°C. Although the hydration process is demonstrated to proceed at a slower rate in previous study [1,8], low temperature still has a significant impact on the dissolution of clinkers and their reaction with water, resulting in delay in setting time.…”
Section: E Setting Timesmentioning
confidence: 97%
“…Cement, as one of the most widely used pavement materials, is widely used in pavement engineering because of its low price and easy availability. However, previous studies have demonstrated that low temperature prolongs the setting time of cement and reduces the strength of cement, resulting in lower construction productivity in cold regions [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Suspension rheology [4][5][6] is discussed, using both experiments and computations. Various aspects of hydration/curing [7][8][9][10][11][12] are explored, again using both experiments and computations. Other topics from this same dual point of view include shrinkage [13][14][15][16], transport (ions, water, heat) [17][18][19][20][21][22][23][24], including probably the first use of Lattice Boltzmann computational methods to construction material application [22,23], and durability/degradation [25][26][27].…”
Section: Cement and Concretementioning
confidence: 99%
“…Cement-stabilized macadam is low-dose cement-base-stabilized mixture and its cement dosage is 5% or so; it is generally used for base layer of pavement construction in China [1]. Whether or not the compressive strength of cement-based materials largely depends upon the curing process is well known, in which both the curing temperature and time are particularly important [2,3]. For conventional laboratory test of compressive strength, the curing is typically carried in constant temperature environment at 20°C in many national specifications [4][5][6].…”
Section: Introductionmentioning
confidence: 99%